Fungal diversity in selected coastal mangrove ecosystems in East Berbice Corentyne, Guyana, South America - Sharif, Wazim R; Silva, Phillip NB Da (GSC Biological and Pharmaceutical Sciences, 2021)
There is limited data on the fungal diversity in mangrove ecosystems in Guyana. This study investigated fungal diversity during the dry season in three selected coastal mangrove ecosystems along the Corentyne Coast of East Berbice, Guyana. Sampling was conducted within randomly established 50 m x 50 m plots containing 20 mini transects of length 12.5 m x 10 m in the overwash mangrove ecosystem at each of six study sites within the three study locations. Samples retrieved from the study plots included leaf, bark, soil and fruiting bodies. These were placed into separate bags and labelled appropriately. Environmental parameters were recorded at each study plot. Fruiting bodies were used to identify macrofungal species, and the leaf, bark and soil were used to prepare cultures from which microfungal samples were identified. The species that were identified were used to compile a checklist of fungal species, and diversity indices were calculated. A total of thirty (30) species were recorded, nine (9) of which were microfungi identified from the cultured samples and twenty-one (21) species were identified from macrofungal fruiting bodies retrieved at the study sites. The results further revealed that an increase in pH and salinity and a decrease in temperature resulted in an increase in species richness. Tidal activity also appeared to reduce species richness. Aspergillus, Rhizopus and Trichoderma were the dominant species at the three study sites with high relative species abundance. There also appeared to be some instances of substrate specificity.